Effect of ZrB2 addition on the oxidation behavior of Si-SiC-ZrB2 composites exposed at 1500°C in air. Issue 1 (January 2018) - D'Amico, Claudio; Bianchi, Giovanni; Padovano, Elisa; Biamino, Sara; Aversa, Alberta; Badini, Claudio; Ortona, Alberto
Background: Silicon carbide ceramics obtained by reactive infiltration of silicon (SRI) have many industrial applications especially involving severe and high temperature conditions. In this study, the oxidation behavior in air of Si-SiC-ZrB2 systems at a high temperature (1500°C) for dwelling times of up to 48 hours was examined. Methods: The oxidation process was analyzed on the basis of elemental maps and X-ray diffraction patterns taken, respectively, on the core and on the surface of the specimens, together with weight gains and the average thicknesses of the resulting scale. Further, flexural strength at room temperature was examined as a function of different oxidation times. Results: The main chemical reactions and phase transformations involved in the oxidation process are reported. Several oxides were detected on the surface: zirconia, silica, zircon and 3-zirconium monoxide. All of the samples showed a parabolic oxidation kinetics, suggesting that the controlling mechanism was the diffusion; however, even after 48 hours, the oxidation process was not finished – indeed, all of the samples continued to gain weight. Conclusions: The oxidation of Si-SiC-ZrB2 material produced via SRI was slower compared with previously investigated ZrB2 -SiC composites processed with a different techniques and tested in similar conditions. The oxidation mechanism was found to be consistent with the convection cells model.